Insight into the role of different extracellular polymeric substances components on trimethoprim adsorption by activated sludge. (15th March 2022) - Ma, You; Yuan, Pei-Kun; Wu, Yu; Meng, Han; Wang, Guo-Xiang; Xie, Wen-Ming; Zhang, Li-Min; Ma, Jie; Xiao, Yan
Abstract: Adsorption is the primary mechanism of antibiotic removal in wastewater treatment plants, wherein the extracellular polymeric substances (EPS) of the activated sludge play an important role. Due to their complex characteristics, the effect of EPS components on antibiotic adsorption is unknown. Therefore, in this study, the role of main components of EPS in antibiotic adsorption was explored using enzymatic treatment. The results revealed that proteinase K and α-amylase can efficiently hydrolyse the proteins and polysaccharides of EPS. The protein content of EPS reduced from 31.25 mg/g VSS to 21.53, 18.75, and 10.76 mg/g VSS, after treatment with proteinase K, α-amylase and their combination, respectively; the polysaccharides content also observed a similar decrease from 15.20 mg/g VSS to 8.22, 7.83, and 6.03 mg/g VSS, respectively. The humic substance in EPS was stable during enzymatic treatment. The equilibrium adsorption capacity of activated sludge treated by enzyme for trimethoprim (TMP)- a typical antibiotic, was significantly increased from 2.19 μg/g VSS to 4.68, 5.34, and 8.36 μg/g VSS after treatment with proteinase K, α-amylase and their mixture. The adsorption process was adequately described by pseudo-second-order kinetic model. A multivariable linear regression model was subsequently used to quantify the adsorption capacity of activated sludge for TMP considering the concentration of EPS components. The modelling and validated results showed that the model could satisfactorily predict the TMP adsorption capacity. The results of this study can provide new insights into the role of EPS on antibiotic transformation in biological wastewater treatment systems. Graphical abstract: Image 1 Highlights: Enzymatic treatment was used to disintegrate extracellular polymeric substances. The equilibrium adsorption capacity of sludge treated by enzyme was determined. A model was developed to quantify the adsorption capacity of EPS components. The model could predict the TMP adsorption capacity with EPS components.